1995
DOI: 10.1136/bjsm.29.2.110
|View full text |Cite
|
Sign up to set email alerts
|

Poor ventilatory response to mild hypoxia may inhibit acclimatization at moderate altitude in elderly patients after carotid surgery.

Abstract: Peripheral chemoreceptors (carotid bodies) are the main sensing organs for hypoxaemia. During carotid surgery, the carotic body in the bifurcation of the common carotid artery is often involved and damaged or destroyed. Animals lose their ability to adapt to high altitude after experimental denervation of the carotid bodies. The objective of our study was to responds to hypoxaemia and not to anaemia or reduced flow. It is, therefore, the main organ for transduction of hypoxic signals in altitude and inducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 5 publications
0
11
0
1
Order By: Relevance
“…Barnard et al (4) also reported increased carotid body activity in cats exposed to hypoxia for 28 days. Furthermore, human subjects who have undergone carotid surgery adapt rather poorly to high altitude (72), further supporting the idea that chemoreflexes are necessary for altitude acclimatization. Tatsumi et al (84) reported decreased responsiveness of the carotid bodies and hypoxic ventilatory response in cats after 3-4 wk of exposure to 5,500-m altitude, suggesting that prolonged altitude exposure leads to diminished ventilatory hypoxic sensitivity, which is in part due to "desensitization" of the carotid body O 2 -sensing mechanisms (92).…”
Section: Peripheral Chemoreceptors and Altitude Acclimatizationmentioning
confidence: 83%
“…Barnard et al (4) also reported increased carotid body activity in cats exposed to hypoxia for 28 days. Furthermore, human subjects who have undergone carotid surgery adapt rather poorly to high altitude (72), further supporting the idea that chemoreflexes are necessary for altitude acclimatization. Tatsumi et al (84) reported decreased responsiveness of the carotid bodies and hypoxic ventilatory response in cats after 3-4 wk of exposure to 5,500-m altitude, suggesting that prolonged altitude exposure leads to diminished ventilatory hypoxic sensitivity, which is in part due to "desensitization" of the carotid body O 2 -sensing mechanisms (92).…”
Section: Peripheral Chemoreceptors and Altitude Acclimatizationmentioning
confidence: 83%
“…VAH is an important physiological adaptation because failure to hyperventilate at high altitude leads to severe hypoxemia. A large body of evidence suggests that carotid body stimulation and the ensuing chemosensory reflex are critical for evoking VAH (9, 19, 63, 266, 280, 340). …”
Section: Ventilatory Adaptation To Hypoxia: O2 Sensing By the Caromentioning
confidence: 99%
“…One group of patients at risk for this phenomenon includes those who have undergone unilateral or bilateral carotid endarterectomy (CEA) as impaired HVR has been documented in this population [192,193]. Roeggla et al , for example, examined the effect of moderate altitude (1600 m) on gas exchange in patients before and after unilateral CEA and found that, following surgery, patients developed worse hypoxemia and less hyperventilation when compared with their presurgery baseline [194]. Such problems may not be limited to post-CEA patients.…”
Section: Chronic Lung Disease At High Altitudementioning
confidence: 99%